A comprehensive company database analysis of biological assay variability. Issue 8 (August 2016) - Kramer, Christian; Dahl, Göran; Tyrchan, Christian; Ulander, Johan
Highlights: Very little is published on the subject of variability in biological assays. Discussions around assay variability are thus usually based on personal beliefs. We performed a reproducibility analysis of all data in the AstraZeneca database. The standard deviations were on average very small, between 0.21 and 0.26 log units. Robust data can be obtained from most commonly applied biological assays. Abstract : Analysis of data from various compounds measured in diverse biological assays is a central part of drug discovery research projects. However, no systematic overview of the variability in biological assays has been published and judgments on assay quality and robustness of data are often based on personal belief and experience within the drug discovery community. To address this we performed a reproducibility analysis of all biological assays at AstraZeneca between 2005 and 2014. We found an average experimental uncertainty of less than a twofold difference and no technologies or assay types had higher variability than others. This work suggests that robust data can be obtained from the most commonly applied biological assays. Abstract : The variability in biological assays used in drug discovery is generally fairly small and not associated with assay type, technology or log D .